Optical hausdorff quantum energy of spherical magnetic particles - Talat Körpinar; Zeliha Körpinar; Hatice özdemir; ALi Akgül; Murad Khan Hassani (Scientific Reports)
Abstract In this article, a new approach for spherical magnetic curves under the spherical system in spherical space is given. Firstly, the Hausdorff derivative of the Lorentz spherical magnetic fields $$φ ( \varvec{β }),$$ $$φ \left( \varvec{t}\right) ,$$ $$φ \left( \varvec{n}\right)$$ of spherical magnetic curves is constructed. On the other hand, the Lorentz spherical magnetic fields, by considering the Hausdorff derivative definition, are presented. Eventually, the Hausdorff energies of these spherical Lorentz fields according to the spherical system in $$\mathbb {S}^{2}$$ spherical space are computed.